All the world's a stage works from the Goetz Collection - Goetz, Ingvild 1941- (Fundación Banco Santander, 2015)
All the World's a stage' showcases works from the Goetz Collection, co-edited by TF Editores and Fundación Banco Santander. It presents a selection of 93 works from the largest collection of contemporary art in Germany, collected during more than thirty years by Ingvild Goetz. Twenty different artists are represented in the show, including Mike Kelley, Ulrike Ottinger, Nan Goldin, Candida Höfer, Cardiff & Miller, Matthew Barney and Elmgreen and Dragset include, among others. All the works, personally selected by the owner of the collection and with the curator of the exhibition, Karsten Lockemann, reflect on the issue of representation, theatre and stage. It shows through various artistic mediums of contemporary art (film, video, photography, installations, sculpture or painting) the dialogue between the performing and visual discipline.